WHAT IS SOCIAL WORK? - Dunajevas, Eugenijus (Socialinė teorija, empirija, politika ir praktika, 2009)
One way to understand and explain social work is to stop searching for the united or single definition of social work and to look at it as multidimensional phenomena. The main dimensions of social work are social work as academic discipline or research and social work as a practice. The first part of the article is designed to present possible or hypothetical taxonomy of social work theories. It is stated that it can be identified 24 types of social work theories. The second part of the article analyses the forms of social work practice. There are four types of social work practice: reformist – individualist, reformist – collectivist, therapeutic – individualist, therapeutic – collectivist. The dominant form of social work practice in contemporary society is known by the name of personal social services.
Keywords: Social work identity; Social work theory; Social work practice; Personal social services